Sustitución de empleador - Puntriano Rosas, César Alfredo (2020)
The purchase of companies, mergers, spin-offs, reorganizations in general, constitute extremely complex operations that impact, of course, the underlying corporate relationships to the companies that are subject to them. There is also a natural effect on the taxation of corporations and people involved. However, a fundamental edge is the effect of said operations on the working relationships of personnel employed by the participating companies. In this article we analyze the aforementioned effect and the existence of responses by our legal system.